Application of School-Based Management in Improving Quality in Junior High Schools - Anif, Muhammad (Graduate Program Magister Manajemen Pendidikan, 2023)
The purpose of this qualitative study was to investigate the implementation of Islamic higher education development management in Indonesia. The study’s findings found that, first, the process of establishing school-based management demonstrated how autonomous, on average, school authority implementation is. Second, the use of participatory decision-making revealed a lack of empowerment in the community; and third, the process of implementing school-based management revealed the involvement of school members and the community in participatory decision-making, which generally involved school members and school committees. The fourth concluded that these educational institutions had implemented the accountability principle, but the outcomes varied due to differences in the degree of adherence to rules, customs when performing tasks, their perceptions of the concept of accountability, the school community’s interest in and encouragement of carrying out accountability, and the values held by the school community. Finally, compared to prior years, there was an increase in high-caliber accomplishments in the 2013-2014 academic year, both academic and non-academic.